Psychological Well-Being of Exchange Program Students - Nova, Dahlia; Yula, Silvia; Lestari, Sri (Bulletin of Counseling and Psychotherapy, 2025)
The objectives of this study are (1) to describe the psychological well-being conditions of students who participated in the student exchange program at Universitas PGRI Madiun; (2) to determine the differences in psychological well-being of students who participate in exchange programs based on gender, and (3) to determine the differences in psychological well-being of students participating in exchange programs based on each dimension of psychological well-being. The subjects of this study were students who participated in the offline student exchange program at Universitas PGRI Madiun, totaling 39 students from 21 universities from 11 regions outside Java. Sampling was done through a purposive sampling technique. Data collection was conducted using Ryff's Psychological Well-Being scale, consisting of 18 items. The results of the reliability test using the Cronbach coefficient test obtained a value of 0.84. The data analysis technique used descriptive statistics. The Mann Whitney test formula was used to determine the difference in psychological well-being in terms of gender. The analysis of variance, was used to determine the differences in each dimension of psychological well-being. The results of the study showed that self-acceptance has the highest level of dimension in psychological well-being.